An examination of PT Bank Negara Indonesia Tbk's capital structure for the years 2014–2022 with respect to profitability, asset structure, company size, and growth opportunities - Achmad, Chaidir; Rangkuti, Zulkifli; Taufik, Kemal (Moneter: Jurnal Keuangan dan Perbankan, 2024)
The aim of this study is to investigate the relationship between the capital structure (debt to equity ratio, or DER) of PT Bank Negara Indonesia Tbk (BNI) and its expansion potential (sales growth), firm size (size), asset structure, and profitability (return on assets, or ROA). The period covered by this investigation is 2014–2022. Secondary information from financial reports accessible at www.idnfinancials.com, www.bni.co.id, and www.idx.co.id on the internet. The method used is multiple regression analysis, where profitability, asset structure, business size, and growth prospects are the independent components and capital structure is the dependent variable. The classic assumption test includes the following criteria: autocorrelation, heteroscedasticity, multicollinearity, and normality. To assess the hypothesis, multiple regression analysis and the partial test (t-test) are then employed. The findings show that capital structure is significantly and negatively impacted by profitability, as shown by the values of tcount> ttable (-37.203 > 2.028); capital structure is significantly and negatively impacted by asset structure (-50.337 > 2.028); capital structure is significantly and positively impacted by company size (1. 808E-009 > 2.028); and capital structure is positively and significantly impacted by growth opportunity (3.195 > 2.028). In addition, there is a R Square value of 79.8% and a value of Fcount> Ftable (30.695 > 2.48).